2017
DOI: 10.1097/aln.0000000000001383
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Anesthesia Has Long-term Consequences on Motor and Behavioral Development in Infant Rhesus Macaques

Abstract: Background Experimental evidence correlates anesthetic exposure during early development with neuronal and glial injury and death, as well as behavioral and cognitive impairments, in young animals. Several, although not all, retrospective human studies of neurocognitive and behavioral disorders after childhood exposure to anesthesia suggest a similar association. Few studies have specifically investigated the effects of infant anesthesia exposure on subsequent neurobehavioral development. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 49 publications
2
83
0
Order By: Relevance
“…Studies in nonhuman primates found that general anesthesia exposure of >5 hours resulted in negative functional and behavioral outcomes. 21,22 Additionally, a recent review reported that more than 80% of animal studies investigating neurotoxicity of general anesthesia found a negative effect after exposure of 3 hours or longer. 23 However, there remains limited information from human studies on the effect of long general anesthesia duration and results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in nonhuman primates found that general anesthesia exposure of >5 hours resulted in negative functional and behavioral outcomes. 21,22 Additionally, a recent review reported that more than 80% of animal studies investigating neurotoxicity of general anesthesia found a negative effect after exposure of 3 hours or longer. 23 However, there remains limited information from human studies on the effect of long general anesthesia duration and results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some studies have also demonstrated long-term behavioral and functional changes in the neurodevelopment of animals exposed to prolonged anesthesia in infancy. 2 There is, however, controversy over whether these animal data are relevant in the care of children undergoing general anesthesia. [3][4][5] The changes seen in preclinical studies are greatest with exposure to gamma-aminobutyric acid (GABA) agonists and N-methyl-Daspartate (NMDA) antagonists such as volatile anesthetics (eg, sevoflurane), propofol, midazolam, ketamine, and nitrous oxide.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent data in non-human primates have provided definitive evidence that early postnatal GA exposure can have lasting effects on cognition, including deficits in socioemotional and learning function [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%